A New Normal - Purchasing Seafood Online: An Investigation of Consumers’ Purchase Intention - Chia-Ying Tan; Yen-Nee Goh; Mao-Seng Ting (Global Journal Al-Thaqafah, 2024)
Grocery nowadays offers fresh and frozen seafood to people in Malaysia on the internet platform. The phenomenon is driven by the growing seafood industry market with 17.4 percent compound annual growth (CAGR). Besides, the phenomenon also helped the rising trend statistics for online retailing as well as the growing market of online grocery. The purpose of this article is to study the direct relationship between the determinants (Attitudes, Freshness, Product Variety, Perceived Risk, Perceived Novelty, and Trust) and online purchase intention towards purchasing fresh seafood. This study also intends to examine the mediating effect of attitudes between the determinants (Perceived Usefulness and Perceived Ease of Use) and online purchase intention towards seafood. Data from 202 samples are collected and analysed using the partial least square methodology via an online survey. The findings showed that attitudes were significantly affected by perceived ease of use and perceived usefulness. Furthermore, Attitudes and Perceived Novelty, freshness, and Trust have a significant effect on online purchase intention of seafood, whereas Product Variety has insignificant effect on purchasing seafood by ordering online. It is also proposed that attitudes have significantly mediated the effects of perceived usefulness and Perceived Ease of use on online purchase intention of seafood. The findings have significant implications for Seafood Company to provide an efficient and effective online grocery website based on the need of online customers.